Verses and Hadiths of Riba Prohibition - Juliana Dwi Putri; Zatadini Paramesti; Malika Fitria Ramadhan (Journal of Indonesian Islamic Studies, 2022)
This article aims to understand the meaning of riba and know the sources of Islamic law from the Qur'an and hadiths governing the prohibition of usury. The method used in writing this article is the library research method. Library research is a method that collects library data, then reads it and records it, after which processing the reading results.  The type of data used in this method of library research is secondary data. This journal discusses the prohibition of riba through verses presented in the Qur'an and hadiths including the stages of the prohibition of usury, types of usury, and verses and hadiths. On the other hand, bank interest, which is one of the pillars of the existence of financial institutions, is considered identical to riba. Financial institutions have become pillars of economic growth. The problem is why the Qur'an forbids usury, while various economic activities "require" the presence of flowers identical to usury. The study found two findings. First, the prohibition of usury in the Qur'an has preceded another, more morally intolerable form of restriction that has broadly impacted great harm in society. Second, the prohibition of usury in the Qur'an has relevance to the real sector of the economy. Therefore, Islam provides rules and recommendations to know the prohibition of usury in order to choose something and prevent things that are prohibited by Allah SWT.